Driving under the influence of cannabis among medical cannabis patients with chronic pain. (1st February 2019) - Bonar, Erin E.; Cranford, James A.; Arterberry, Brooke J.; Walton, Maureen A.; Bohnert, Kipling M.; Ilgen, Mark A.
Highlights: We examined 3 measures of driving under the influence of cannabis (DUIC). Adults with chronic pain were seeking medical cannabis certification. Past 6-month DUIC rates were: 56% within 2 h, 51% a little high, 21% very high. Prevalence of DUIC was high and interventions should be developed for prevention. Abstract: Background: Driving under the influence of cannabis (DUIC) is a public health concern among those using medical cannabis. Understanding behaviors contributing to DUIC can inform prevention efforts. We evaluated three past 6-month DUIC behaviors among medical cannabis users with chronic pain. Methods: Adults ( N  = 790) seeking medical cannabis certification or recertification for moderate/severe pain were recruited from February 2014 through June 2015 at Michigan medical cannabis clinics. About half of participants were male (52%) and 81% were White; their Mean age was 45.8 years. Participants completed survey measures of DUIC (driving within 2 h of use, driving while "a little high, " and driving while "very high") and background factors (demographics, alcohol use, etc.). Unadjusted and adjusted logistic regressions were used to examine correlates of DUIC. Results: For the past 6 months, DUIC within 2 h of use was reported by 56.4% of the sample, DUIC while a "little high" was reported by 50.5%, and "very high" was reported by 21.1%. Greater cannabis quantity consumed and binge drinking were generally associated with DUIC behaviors. Higher pain was associated with lower likelihood of DUIC. Findings vary somewhat across DUIC measures. Conclusions: The prevalence of DUIC is concerning, with more research needed on how to best measure DUIC. Prevention messaging for DUIC may be enhanced by addressing alcohol co-consumption.